2012
DOI: 10.1371/journal.pone.0047203
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Collaborative Activities between Non-Professional Disaster Volunteers and Victims of Earthquake Disasters

Abstract: BackgroundAssistance from non-professional disaster volunteers (hereinafter, volunteers) is essential for disaster victims to recover physically and rebuild their lives; however, disaster victims in some areas are reluctant to accept assistance from volunteers. This study explored factors that may influence collaborative activities between volunteers and victims of earthquake disasters.MethodsFrom July to September 2008, a self-reporting questionnaire survey was conducted with all 302 leaders of neighborhood a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 8 publications
0
29
0
1
Order By: Relevance
“…Responses to each question were scored on a Likert-type scale ranging from 1 to 7, with higher scores indicating stronger SOC. In Japanese studies, the Cronbach's alpha of the SOC-UTHS was ranged from 0.82 to 0.84 7,8) ; furthermore, it was significantly associated with the SOC-13 8) . Psychological distress was evaluated by the 28-item version of the General Health Questionnaire (GHQ) 9) .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Responses to each question were scored on a Likert-type scale ranging from 1 to 7, with higher scores indicating stronger SOC. In Japanese studies, the Cronbach's alpha of the SOC-UTHS was ranged from 0.82 to 0.84 7,8) ; furthermore, it was significantly associated with the SOC-13 8) . Psychological distress was evaluated by the 28-item version of the General Health Questionnaire (GHQ) 9) .…”
Section: Methodsmentioning
confidence: 97%
“…SOC was assessed using a shortened version of Antonovsky's SOC questionnaire, the University of Tokyo Health Sociology version of the SOC scale (SOC-UTHS) 7,8) . Responses to each question were scored on a Likert-type scale ranging from 1 to 7, with higher scores indicating stronger SOC.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are limited research work with regards general disaster preparedness with some few published researches on specific disaster preparedness topics such as heat waves and climate change; collaborative activities between non-professional disaster volunteers and victims of earthquake disasters; climate change and climate variability; as well as preparation of health care workers for disasters (Haraoka et al, 2012;Akompab et al, 2013;Semenza, Ploubidis, George, 2011;Ogedegbe, 2012). In addition, a review of the literatures revealed that there is a paucity of published papers that attempts to develop and validate instruments aimed at measuring General Disaster Preparedness Belief (GDPB) using the health behavior models as a theoretical framework.…”
Section: Introductionmentioning
confidence: 99%
“…The perceived severity of the disaster -how organizations and people conceive it in terms of consequences, scope and magnitude -is crucial for what kinds of plans that are developed (Witte 1998;Weinstein 2000;Haraoka et al 2012). Whether the causes of a disaster are seen as natural or man-made is central for what preventive measures are seen as relevant, as well as for attribution of responsibility (Erikson 1994;Freudenberg 1997).…”
Section: Resultsmentioning
confidence: 99%